Model Matematika SEIRS Penyebaran Penyakit Pneumonia pada Balita dengan Pengaruh Vaksinasi - Aly Muhammad Zhafran; Arnellis Arnellis (Journal of Mathematics UNP, 2022)
This study aims to establish a mathematical model of the distribution of pneumonia in children under five using the SEIRS (Susceptible-Exposed-Infected-Recovered-Susceptible) model, model analysis, and comparison of minimal vaccinations. This model consists of several classes, namely susceptible, infected but not yet infectious, infected, and cured. Analysis of the stability of the model is obtained by finding a disease-free fixed point whose analysis results are asymptotically stable and an endemic fixed point whose analysis results are asymptotically stable if the value of  A>(Cαβmσ-Cαβσ)/(BCm-Bmρ) and A>βγρ/BC .